Self-Directed Learning in Medical Education: Training for a Lifetime of Discovery. Issue 5 (20th October 2022) - Ricotta, Daniel N.; Richards, Jeremy B.; Atkins, K. Meredith; Hayes, Margaret M.; McOwen, Katherine; Soffler, Morgan I.; Tibbles, Carrie D.; Whelan, Alison J.; Schwartzstein, Richard M.; ,
Abstract: Issue : Life-long learning is a skill that is central to competent health professionals, and medical educators have sought to understand how adult professionals learn, adapt to new information, and independently seek to learn more. Accrediting bodies now mandate that training programs teach in ways that promote self-directed learning (SDL) but do not provide adequate guidance on how to address this requirement. Evidence : The model for the SDL mandate in physician training is based mostly on early childhood and secondary education evidence and literature, and may not capture the unique environment of medical training and clinical education. Furthermore, there is uncertainty about how medical schools and postgraduate training programs should implement and evaluate SDL educational interventions. The Shapiro Institute for Education and Research, in conjunction with the Association of American Medical Colleges, convened teams from eight medical schools from North America to address the challenge of defining, implementing, and evaluating SDL and the structures needed to nurture and support its development in health professional training. Implications : In this commentary, the authors describe SDL in Medical Education, (SDL-ME), which is a construct of learning and pedagogy specific to medical students and physicians in training. SDL-ME builds on the foundations of SDL and self-regulated learning theory, but is specifically contextualized for the unique responsibilities of physicians to patients, inter-professional teams, and society. Through consensus, the authors offer suggestions for training programs to teach and evaluate SDL-ME. To teach self-directed learning requires placing the construct in the context of patient care and of an obligation to society at large. The SDL-ME construct builds upon SDL and SRL frameworks and suggests SDL as foundational to health professional identity formation. KEYWORDSself-directed learning; graduate medical education; undergraduate medical education; theoretical frameworks Supplemental data for this article is available online at https://doi.org/10.1080/10401334.2021.1938074 .